Environmental Thought in the Vedas, Ramayana, and Mahabharata: A Review-Based Perspective: वेद-रामायण-महाभारतादिग्रन्थेषु पर्यावरणचिन्तनम् : एकसमीक्षात्मकदृष्टिः - Meena, Jitendra Kumar (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The present research paper titled “Environmental Thought in the Vedas, Ramayana, and Mahabharata: A Review-Based Perspective” critically analyzes the profound approach towards nature embedded in ancient Indian literature. The Vedas present a philosophical model of ecological balance through the deification of the five great elements (Panchamahabhutas) and the Yajna cycle. In the Ramayana, the depiction of Lord Rama's forest exile embodies the spirit of coexistence with nature; the portrayal of Panchavati’s environment during Sita’s abduction and Jatayu’s role in protection emphasizes that nature is not merely a resource but a companion with emotional kinship. In the Mahabharata, the environmental ethics of Yudhishthira, rooted in righteousness, reflect through his commitment to tree plantation, reverence for Mother Earth, and the teachings of Bhishma in the Anushasana Parva, which establish a moral foundation for environmental protection. A comparative analysis reveals that the Vedas offer a philosophical vision, the Ramayana emphasizes coexistence, and the Mahabharata highlights ethical responsibility, each presenting diverse dimensions of ecological thinking. In the current context—marked by climate change, pollution, and deforestation as pressing threats to human life—these ancient perspectives of coexistence, reciprocal bonds (Rinanubandha), and ecological equality may serve as potential pathways toward sustainable solutions. Thus, these texts are not merely religious scriptures but living sources of philosophical thought and environmental ethics.Abstract in Sanskrit Language: "वेद-रामायण-महाभारतादिग्रन्थेषु पर्यावरणचिन्तनम् : एकसमीक्षात्मकदृष्टिः" इत्यस्मिन् शोधपत्रे प्राचीनभारतीयसाहित्ये प्रकृतिप्रति यः गम्भीरः दृष्टिकोणः अस्ति, सः समीक्षात्मकदृष्ट्या विवेचितः अस्ति। वेदेषु पंचमहाभूतानां दैवीकरणेन, यज्ञीयचक्रेण च पर्यावरणसन्तुलनस्य तात्त्विकं रूपं प्रतिपादितम् अस्ति। रामायणे रामस्य वनवासे सहजीवनस्य भावना, सीताहरणे पंचवटीप्रकृतेः चित्रणं, जटायोः संरक्षणदृष्टिः च दर्शयन्ति यत् प्रकृतिः केवलं संसाधनं न, अपि तु आत्मीयं सहचर्यं अस्ति। महाभारते धर्मराज्ये स्थितस्य युधिष्ठिरस्य वृक्षारोपणसम्बद्धा धर्मनिष्ठा, भूमेः मातृत्वबोधः, तथा अनुशासनपर्वे भीष्मस्य उपदेशाः पर्यावरणसुरक्षायाः नैतिकाधारं स्थापयन्ति। तुलनात्मकदृष्ट्या ज्ञायते यत् वेदेषु दर्शनं, रामायणे सहअस्तित्वम्, महाभारते नीतिनिष्ठा पर्यावरणचिन्तनस्य विविधान् आयामान् प्रदर्शयन्ति। अद्यतनसन्दर्भे, यदा जलवायुपरिवर्तनं, प्रदूषणम्, वनविनाशः च मानवजीवनस्य संकटरूपेण प्रतितिष्ठन्ते, तदा एषः प्राचीनदृष्टिकोणः—सहअस्तित्वं, ऋणानुबंधः, जैविकसमत्वम् च—मानवता हेतोः समाधानदायी मार्गः भवितुं शक्नोति। अतः, एते ग्रन्थाः केवलं धार्मिकपठ्यवस्तूनि न, अपि तु जीवनचिन्तनस्य, पर्यावरणनैतिकतायाः च जीवन्तस्रोतांसि सन्ति।Keywords: रामायणम्, महाभारतम् ,पर्यावरणचिन्तनम्, जैवविविधता, प्रकृतिसंरक्षणम्
Keywords: Ramayana; Mahabharata; Environmental Thought; Biodiversity; Nature Conservation